Separation of five flavonoids with similar polarity from Caragana korshinskii Kom. by preparative high speed counter‐current chromatography with recycling and heart cut mode. Issue 19 (9th August 2020) - Ma, Yumei; Yang, Xue; Chen, Jilin; Zhao, Jingyang; Yang, Li; Yan, Shuping; Li, Hongmei; Shen, Cheng; Wei, Yangfei; Wang, Shuo; Chen, Tao; Chen, Zhi; et al.
Abstract: Five flavonoids with similar polarity were obtained from Caragana korshinskii Kom. by preparative high speed counter‐current chromatography. Due to their similar polarity, it is difficult to select a suitable solvent system for one‐step separation. Three fractions including one pure compound were only obtained with a relatively suitable solvent system of ethyl acetate: n ‐butanol:water (0.5% glacial acetic acid) (4:6:10, v:v:v). In order to improve the separation efficiency, recycling and heart cut modes were introduced. As a result, two flavonoids with separation factor value at 1.13 and the other two with separation factor value at 1.20 were successfully separated. Finally, five flavonoids with purity higher than 98% were obtained. Fortunately, a new compound named myricetin 3′‐methyl ether 3‐ O ‐glucoside‐7‐ O ‐rhamnoside was obtained. The results indicated that the recycling combined with heart‐cut mode could be effective for the preparation of natural compounds with similar polarity.